La pêche en rivière en Martinique : quels sont les enjeux d’une patrimonialisation socio-environnementale ? - Bertrand Morandi; Anne Rivière-Honegger; Marylise Cottet (Études Caribéennes)
River fishing is prohibited in Martinique for a decade due to chlordecone pollution. Argument of inheritage values of river fishing rises in the context of discussion of re-authorization and regulation of this activity. Fishing would be a socio-environmental inheritage due to its social and cultural values but also to its assumed function of driver of man-river interactions. Fishing would reinforce closeness to river and favor implication in their environmental preservation. In this paper, we change these assertions about inheritage values of river fishing into research questions. Our work focuses on of river fishing activities in order to provide useful information to productive discussion about the patrimonialization process of river fishing. In this way, we use complementary materials from semi-structured interview survey and documentary study. These materials are analyzed with both qualitative and quantitative methods. Given the results, we highlight diversity of river fishing activities and their recent evolution trend from fishing for resource to fishing leads by recreational interest. We discuss about the creoleness of fishing technics and tools traditionally considered as Native American direct heritage. Finally, we question the specific but non-exclusive role of fishing activities to maintain close link between Martiniquans and rivers.